The enzymology of sludge solubilisation under biosulphidogenic conditions : isolation, characterisation and partial purification of endoglucanases - Oyekola, Oluwaseun Oyekanmi (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2004)
Endoglucanases play an important function in cellulose hydrolysis and catalyse the initial attack on the polymer by randomly hydrolysing the Î²-1,4 glucosidic bonds within the amorphous regions of cellulose chains. Cellulolytic bacteria have been isolated and characterised from the sewage sludge and the activation of several hydrolytic enzymes under biosulphidogenic conditions of sewage hydrolysis has been reported. The aims of this study were to: identify, induce production, locate and isolate, characterise (physicochemical and kinetic) and purify endoglucanases from anaerobic biosulphidogenic sludge. The endoglucanase activities were shown to be associated with the pellet particulate matter and exhibited a pH optimum of 6 and temperature optimum of 50 Â°C. The enzymes were thermally more stable when immobilised to the floc matrix of the sludge than when they were released into the aqueous solution via sonication. For both immobilised and released enzymes, sulphate was slightly inhibitory; activity was reduced to 84 % and 77.5 % of the initial activity at sulphate concentrations between 200 and 1000 mg/l, respectively. Sulphite was stimulatory to the immobilised enzymes between 200 and 1000 mg/l. Sulphide stimulated the activities of the immobilised endoglucanases, but inhibited activities of the soluble enzymes above 200 mg/l. The enzyme fraction did not hydrolyse avicel (a crystalline substrate), indicating the absence of any exocellulase activity. For CMC (carboxymethylcellulose) and HEC (hydroxylethylcellulose) the enzyme had K_m,app_ values of 4 and 5.1 mg/ml respectively and V_max,app_ values of 0.297 and 0.185 Î¼mol/min/ml respectively. Divalent ions (CuÂ²â º, NiÂ²â º and ZnÂ²â º) proved to be inhibitory while FeÂ²â º, MgÂ²â º and CaÂ²â º stimulated the enzyme at concentrations between 200 and 1000 mg/l. All the volatile fatty acids studied (acetic acid, butyric acid, propionic acid and valeric acid) inhibited the enzymes, with acetic acid eliciting the highest degree of inhibition. Sonication released ~74.9 % of the total enzyme activities into solution and this was partially purified by PEG 20 000 concentration followed by DEAE-Cellulose ion exchange chromatography, which resulted in an appreciable purity as measured by the purification factor, 25.4 fold.
Keywords: Sewage -- Purification -- Anaerobic treatment; Anaerobic bacteria; Sewage sludge; Hydrolysis